Genomic characterization of a rotavirus G8P[1] detected in a child with diarrhea reveal direct animal-to-human transmission - Martinez, Magaly (2014)
Group A rotavirus is a major cause of severe gastroenteritis in children and young animals. During a retrospective analysis of samples collected from Paraguayan children under 5 years old with diarrhea, and previously negative for rotavirus and norovirus, we detected the presence of bovine rotavirus sequences by viral metagenomics. Nucleic acid was extracted direct from stool sample and determined to be G8P[1]. The genomic analyzes revealed that the strain presents an Artiodactyl-like genome (G8-P[1]-I2-R2-C2-M1-Ax-N2-T6-E12-H3) suggesting a direct animal-to-human transmission.